Evaluation of quali-quantitative research methods and instruments through multidimensional analysis of pilot-application - Vazzoler - Mendonça, Adriana [UNESP]; Rondini, Carina Alexandra [UNESP]; Costa - Lobo, Cristina (Revista Meta - Avaliacao, 2024)
Piloting is a methodological resource that can assess and refine a research project prior to its execution. The purpose of this paper is to describe the pilot-application of a research study whose general objective was to understand the profile of university students who won medals in science olympics. The pilot tested the applicability of standardized instruments and the effectiveness of instruments created to obtain data from the sample and to conduct interviews. The method of analysis considered the ethical, methodological, operational, theoretical, analytical, and representational dimensions. The results led to modifications in the created instruments and procedures. For future research, it is recommended to design pilots with more participants, more than one consecutive pilot-application, and to include the researcher's perceptions.
Avaliação dos métodos e instrumentos de pesquisa qualiquantitativa por meio de análise multidimensional da aplicação-piloto
Keywords: Data collection procedures; Medalists in scientific olympics; Pilot-study; Research design; Semi-structured interview